Blood Metabolomics Analysis Identifies Differential Serum Metabolites in Elite and Sub-elite Swimmers - Cai, Ming; Wu, Chao; Jing, Chen; Shen, Xunzhang; He, Mian; Wang, Liyan; Guo, Qi; Yan, Yan; Yan, Xu; Yang, Ruoyu (Frontiers in Physiology, 2022)
Objective: Metabolites in body fluids, such as lactate, glucose and creatinine, have been measured by conventional methods to evaluate physical function and performance or athletic status. The objectives of the current study were to explore the novel metabolite biomarkers in professional swimmers with different competition level using nuclear magnetic resonance (NMR) metabolomics, and try to establish a model to identify athletic status or predict the competitive potential. Methods: Serum samples were collected from 103 elite and 84 sub-elite level Chinese professional swimmers, and were profiled by NMR analysis. Results: Out of the thirty-six serum metabolites profiled, ten were associated with the athletic status of swimmers (with P<0.05). When compared with sub-elite swimmers, elite swimmers had higher levels of high-density lipoprotein (HDL), unsaturated fatty acid, lactic acid and methanol. Elite swimmers had lower levels of isoleucine, 3-hydroxybutyric acid, acetoacetate, glutamine, glycine and α-glucose. A model with four metabolites, including HDL, glutamine, methanol and α-glucose, was established to predict athletic status, by adjusting with different covariates. The area under curve (AUC) of the best model was 0.904 (95% CI: 0.862-0.947), with a sensitivity and specificity of 75.5% and 90.2%, respectively. Conclusion: we have identified ten metabolite biomarkers with different levels between elite and sub-elite swimmers, the differences could result from genetic or training differences between the two cohorts. A model with four metabolites has successfully differentiated professional swimmers with different competitive levels.